The implementation of inclusive design for public buildings in Kota Kinabalu, Sabah - J Julius; L Gungat; I Tukiman (IOPSciences, 2022)
Inclusive design is a main aspect in designing public buildings. Lack of accessibilities (ramp entrance, task lighting, lever door handles and etc.) as part of inclusive design methodology in public buildings used by the people for any purpose, such as, education, entertainment, worship or assembly has decreased a quality of international standard building design which directly has effected end user’s lifestyle, time and money. As the demand to equip our public building with inclusive design facilities has increased due to rapid population growth. Hence, this research paper presents the inclusive design implementation in the existing public buildings in Kota Kinabalu, Sabah which includes identification of design barriers and challenges for persons with disabilities (PWDs), children, elders and caretakers. In summary, this study identified the lack of inclusive design elements for buildings built in the 1980s, where the enactment of the Persons with Disabilities Act 2008 was only enforced on July 7, 2008. Therefore, these buildings improvement will keep people’s diversity and uniqueness by experts proper planning based on experience and feedback which can be found in buildings built in the 2009 and later.